Teachers’ Perceptions of Successful Online Learning in Teaching English Classroom during Covid-19 - Herlina, Herlina; Al Fauzi, Fatih; Mahbub, Moh. Arif (Linguapedia, 2023)
Abstract. The purpose of this study was to find out the teacher's perception of the success of online learning in English lessons. The results of the interviews with the two subject teachers are presented in the form of a description because the data collected is part of the teacher's experience and the data is obtained from interviews with the teacher being told. The results of research on teacher perceptions of online-based English learning or distance learning. Interview data were taken from two sources, namely the VII grade English teacher and the VIII grade English teacher of private junior high school in Probolinggo, East Java. Every teacher needs to prepare a lesson plan or organize class activities before class begins. The learning process consists of several processes, namely: planning, implementing, and evaluating learning. The main focus of this research is online learning in English subject.